Occurrence of Staphylococcus aureus in raw milk produced in dairy farms in São Paulo state, Brazil - Fagundes, Helena; Barchesi, Luciana; Nader Filho, Antonio; Ferreira, Luciano Menezes [UNESP]; Oliveira, Carlos Augusto Fernandes (Sociedade Brasileira de Microbiologia, 2010)
The objective of the present study was to evaluate the occurrence of Staphylococcus aureus in milk produced in 37 farms located in the regions of Ribeirão Preto and São Carlos, state of São Paulo, Brazil. Two-hundred and eight samples of milk from individual cows showing subclinical mastitis, and 37 samples of bulk tank milk were analyzed. S. aureus strains were detected in 18 (7.3%) milk samples: 14 (6.7%) from samples of individual cows, and 4 (10.8%) from bulk tank milk. Two individual milk samples (14.3%) and two bulk milk samples contained enterotoxigenic S. aureus. PFGE analysis revealed the genetic heterogeneity of the strains isolated from raw milk, which presented to 13 S. aureus patterns. Results confirmed the potential transmission of staphylococcal food poisoning to consumers via milk of cows affected by subclinical mastitis, mainly when raw milk is ingested.
Keywords: Staphylococcus aureus; Raw milk; Bovine; Mastitis; enterotoxin